Islamic home financing in Malaysia: an overview of Islamic finance concepts applied - Hasmad, Nurjannah; Alosman, Abdulrahman (Perkumpulan Dosen Fakultas Agama Islam Indramayu dan Asosiasi Dosen DPK) UIN Sunan Gunung Djati Bandung, 2022)
Owning a house is an essential decision in one’s life. With various house financing products offered by financial institutions, products that adhere to the Shariah principles termed as Shariah-compliant became an alternative for Muslim consumers to avoid being involved in transactions related to usury (riba). This paper aims to provide an overview of the Islamic finance concepts applied in Islamic home financing products in Malaysia namely Ba’i Bithaman Ajil (BBA), Musharakah Mutanaqisah (MM) and Tawarruq. This study employs qualitative approach using library research method by examining and analyzing secondary data collected from multiple sources such as journal articles, policy documents, books, resolutions, standards, product disclosure sheets and reports. Results of this study revealed that acceptance of scholars on Shariah finance concept applied in Islamic home financing in Malaysia varies in degree for each concept with MM being the less disputable one among the three. The evolvement trend of these concepts emerges from debt-based BBA to equity-based MM and back to a debt-based one; Tawarruq. The results also found that even when applying the Shariah concept in the operation of Islamic home financing products, banks cannot yet escape from using interest-based benchmarks in calculating their profit. It is concluded that Islamic banks are exerting a commendable effort in providing Shariah alternatives for home financing, however, this effort needs to be improved to provide a Shariah-compliant home financing that carefully observes the Shariah requirement and at the same time more affordable to consumers than conventional loans. The authors suggest that future research will try to propose a less disputable Shariah compliant product for Islamic home financing which are more cost-effective to the buyer and at the same time profitable to the Islamic financial institutions